The Translation Variations and Quality of Wh-Question in Daily Routines Expressions - Azis Abdul Gofur; saehu, andang; Ujang Suyatman (Institut Agama Islam Negeri Palopo, 2024)
This study aims at reporting the translation variations and qualities provided to wh-questions of daily routine expressions. The study employed descriptive qualitative research method to reveal translation methods and accuracy level produced by 10 students in resulting the translation variations of wh-questions in daily routine expressions. 10 data were collected from Anwarsyah’s book (2019) consisting of what-question (02), who-question (01), when-question (03), where-question (01), why-question (01), and how-question (02). The findings of study show that the majority of students (06) applied transposition mixed with modulation translation techniques. Meanwhile, the rests (04) used literal and free translation methods. Although they have demonstrated their ability to apply various translation strategies, the quality of their translations remains at a moderate level. This is evidenced by the analysis results, which show that their translations are lacking in accuracy, acceptability, and readability.